Primary Tumor Resection Improves Survival in Patients With Metastatic Gastrointestinal Stromal Tumors: A Preliminary Population-Based Analysis - Zhao, Si; Zhu, Hanlong; Jiao, Ruonan; Wu, Xueru; Zhang, Xiuhua; Ji, Guozhong (Frontiers in Oncology, 2020)
Background: Surgery has been the primary treatment in patients with localized gastrointestinal stromal tumors (GISTs) for many decades, whereas it remains controversial regarding the efficacy of primary tumor resection for metastatic GISTs treated with chemotherapy, and likewise it is unclear who would benefit from the surgical resection. Methods: GISTs patients with distant metastases were identified from the Surveillance, Epidemiology, and End Results (SEER) database between 2010 and 2016. Cox proportional hazards regression models were used to identify prognostic factors of overall survival (OS) and cancer-specific survival (CSS). Kaplan-Meier analyses and log-rank tests were conducted to assess the effectiveness of surgery on survival. Results: In total, of 455 patients with metastatic GISTs, 235 patients (51.6%) underwent primary tumor resection and 220 patients (48.4%) did not. Median survival of patients in resection group was 72 (95% CI: 62.90-81.10) months versus 40 (95% CI: 29.53-50.47) months for those in non-resection group (p<0.001). Similarly, surgery in conjunction with chemotherapy led to a favorable impact on survival than chemotherapy alone (OS: 72 vs. 40 months, p<0.001; CSS: 74 vs. 44 months, p<0.001). Multivariable analysis showed that both OS ((HR: 0.581, 95% CI: 0.386-0.874, p=0.009) and CSS (HR: 0.663, 95% CI: 0.439-0.912, p=0.042) were dramatically improved in patients with surgical removal of primary site, as well as primary tumor size between 5-10 cm, while increasing age was predictive of poorer survival. Stratified analysis revealed that patients with tumor locations in the stomach demonstrated a prolonged survival after surgery, with no significant differential surgical effect between the stomach and small intestine.. Conclusions: Our study preliminarily suggests that carefully selected patients with metastatic GISTs might prolong survival after treatment of surgery, especially those with a primary tumor between 5-10 cm and a tumor located in the stomach.